Ethical Issues in E-Business
DOI: 10.4018/978-1-61520-615-5.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Moral Guidelines for Marketing Good Corporate Conduct Online

Abstract: Corporate social responsibility (CSR) is highly valuable for transnational corporations, but entails special requirements of heightened honesty in the marketing of CSR as compared to other goods and services. Companies need help in finding appropriate venues for advertising CSR. The Internet is an ideal medium for advertising CSR because it affords a global reach and greater space than the confines of standard advertising venues. However, using the Internet also poses special challenges in terms of perceived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Stoll (2002) clarifies this issue, writing that the ethics of marketing good corporate conduct have much higher expectations than what we find morally permissible in marketing products. Typical product marketing often employs creative license and exaggerated claims to create desire in potential customers for goods and services.…”
Section: Nike's Counterpointmentioning
confidence: 93%
See 3 more Smart Citations
“…Stoll (2002) clarifies this issue, writing that the ethics of marketing good corporate conduct have much higher expectations than what we find morally permissible in marketing products. Typical product marketing often employs creative license and exaggerated claims to create desire in potential customers for goods and services.…”
Section: Nike's Counterpointmentioning
confidence: 93%
“…Stoll (2002) suggests that the reporting of good corporate conduct should coincide with openness to external financial audits, which help ensure a more complete record of company activity and provide third party credibility to the assertions. Additionally, much research has been conducted regarding the morality and effects of corporate codes of ethics, a common way companies express social responsibility intentions.…”
Section: Nike's Counterpointmentioning
confidence: 98%
See 2 more Smart Citations
“…While no studies have demonstrated a direct link between these consumer-oriented values and positive psychological dispositions, a considerable body of work establishes links between positive psychological domains such as spirituality (Cavanagh and Bandsuch, 2002;Epstein, 2002;Giacalone and Jurkiewicz, 2003;Jackson, 1999;Jurkiewicz and Giacalone, 2004), corporate character (Stoll, 2002), and minimizing self-interest (Carson, 2003) with business ethics. Nonetheless, there are strong theoretical reasons why positive psychology should be linked to CSCSP.…”
Section: Consumer Sensitivity To Corporate Social Performancementioning
confidence: 96%